Factor XI as a Target for New Anticoagulants - Fredenburgh, James C.; Weitz, Jeffrey I. (Hämostaseologie, 2021)
Despite advances in anticoagulant therapy, thrombosis remains the leading cause of morbidity and mortality worldwide. Heparin and vitamin K antagonists (VKAs), the first anticoagulants to be used successfully for the prevention and treatment of thrombosis, are associated with a risk of bleeding. These agents target multiple coagulation factors. Thus, by activating antithrombin, heparin mainly inhibits factor Xa and thrombin, whereas VKAs lower the levels of the vitamin K–dependent clotting factors. Direct oral anticoagulants, which have replaced VKAs for many indications, inhibit only factor Xa or thrombin. Although the direct oral anticoagulants are associated with less bleeding than VKAs, bleeding remains their major side effect. Epidemiological and animal studies have identified factor XI as a target for potentially safer anticoagulant drugs because factor XI deficiency or inhibition protects against thrombosis and is associated with little or no bleeding. Several factor XI–directed strategies are currently under investigation. This article (1) reviews the rationale for the development of factor XI inhibitors, (2) identifies the agents in most advanced stages of development, (3) describes the results of completed clinical trials and provides a summary of those underway, and (4) highlights the opportunities and challenges for this next generation of anticoagulants.
Keywords: anticoagulant; coagulation; factor XI; thrombosis